Geospatial Assessment of the Effect of Gold Mining in Atakunmosa East Local Government Area, Osun State. - Paul Tomilola Elufisan (African Journal on Land Policy and Geospatial Sciences)
This study examined the spatial distribution of the gold mining site in Iperindo; assessed the spatial pattern of the land condition in the study area; and analyzed the effects of Segilola Gold Mining Site on Landuse and Landcover in the study area. The spatial distribution of the mining site was determined using a differential GPS receiver. The spatio-temporal assessment of the mining sites was done using Landsat imageries spanning six years (2019 - 2024). Digital Image Processing (DIP) was done using a supervised classification method. The spatial extent of gold mining sites in Iperindo was determined through the digitization of the boundary of the mining sites on the classified images of the study years. Spatio-temporal landuse and landcover maps were also assessed from the classified images derived from DIP. The effects of gold mining sites on landuse and landcover in Iperindo was carried out by overlaying and comparing the landuse and landcover of the mining areas before the year of commencement of operation (year 2019) and the years of operation (years 2020, 2021, 2022, 2023 and 2024). The results showed that Segilola gold mining site has been increasing in spatial extent from the year 2020 (year of commencement of operation) to the year 2024. The spatial pattern of the land condition in the study area revealed that the landuse and landcover dynamics of the study area within the period under review has greatly been altered, while bare land and the built-up area has increased. This study concluded that Segilola Gold Mining site has been able to alter the landuse and landcover within its location, as landuse and landcover types such as rock outcrop, shrub, forest and a little portion of built-up area had been transformed into bare land. It was therefore recommended that a post-impact assessment should be carried out on the Segilola gold mining site due to its expansion and alteration of landuse and landcover in Iperindo as identified in this study, to mitigate the adverse effects of gold mining.